PENGARUH MEROKOK TERHADAP FAAL PARU - Basuki, Sri Wahyu; Nilawati, Dona Dewi (Universitas Muhamadiyah Surakarta, 2011)
Indonesia is thethirdlargestcigaretteusersafter Chinaand India,which reached 146.86 million inhabitants. Smoking behavior is engulï¬Â ng all circles, including children. Dangers of smoking are undoubtedly makes a person not a long life. When compared with non smokers, smokers aged on average 10 years shorter and spend millions of dollars. Inhaled cigarette smoke may accelerate the decline in lung physiology caused by changes in the structure and function of the airway or parenchyma (tissue) in the lung. The objective of this study was to determine differences in pulmonary function (Vital Capacity/VC, Forced Vital Capacity/FVC, and Forced Vital Capacity of the ï¬Â rst second/FEV1) in male smokers and non smokers at the Medical Faculty of uhammadiyah University of Surakarta and determine the effect of smoking on pulmonary function. This study used analytical research design with cross sectional approach. The subject of this study was the active student and employee at the Medicine Faculty, Muhammadiyah University of Surakarta. Purposive sampling method was random sampling. The results were tested by statistical tests of independent t-test with SPSS 16.0.The sample size obtained was 40Â people consisted of 20 (50%) sample of smokers and 20 (50%) sample of non-smokers. There was not difference VC between male smokers and nonsmokers with p = 0.390. There was difference FVC between male smokers and nonsmokers with p = 0.000. There was difference FEV1 between male smokers and nonsmokers with p = 0.025.This study showed the difference in FVC and FEV1 between male smokers and nonsmokers in the Medicine Faculty, Muhammadiyah University of Surakarta, but VC did not.